Direct and Indirect Factors Influencing Selection of Birthing Attendants in Gunungsari, West Lombok (NTB) - Ni Nyoman Aryaniti; Luh Putu Lila Wulandari; I Nyoman Mangku Karmaya (Universitas Udayana, 2014)
Background and purpose: This study aims to determine the direct and indirect factors influencing the selection of birth attendants in Gunungsari subdistrict, West Lombok. Methods: This study was cross-sectional with a purposively selected sample of 27 mothers giving birth assisted by non-health professionals. Samples of those assisted by health professionals were taken by means of proportional systematic random sampling in Gunungsari and Penimbung health centers, respectively 29 of 916 and 14 of 437. Exogenous factors were maternal education levels, attendance to ANC classes, knowledge levels regarding to birthing attendants, maternal attitude, family support, and access to facilities. Birth attendant selection was the endogenous factor. Data were collected by means of interviews. Data analysis includes descriptive and inferential analysis with path analysis by linear regression. Results: The majority of respondents were 21-25 years old (87.4%), housewives (47.14%) had education under high school (65.72%) and were married (88.57%). Family support had a direct influence in decision making with a coefficient of 0.534 and 35.54% influence overall. Attendance to ANC classes in addition to family support had an indirect influence with a coefficient of 0.520 and 34.78% influence overall. Family support had a direct influence and the factor of attendance to ANC classes and family support has an indirect effect with the overall effect of 70.32%. Conclusion: The presence of the husband/family was needed in ANC class, through an implementation of schedule agreement.